Efficacy and safety of intensive blood pressure control in patients over 60 years: A systematic review and meta-analysis - Huarong Yang; Haiyan Xing; Xue Zou; Meihua Jin; Yang Li; Ke Xiao; Li Cai; Yao Liu; Xue Yang (Clinical and Experimental Hypertension)
Objectives To evaluate the efficacy and safety of intensive blood pressure control in patients over 60 years.Methods Databases including PubMed, Embase and Cochrane library were searched from inception through February 1, 2024. Randomized controlled trials evaluating the efficacy or safety of intensive blood pressure control in patients over 60 years were included in the meta-analysis.Results Intensive blood pressure control in individuals with mild hypertension has been shown to reduce the risk of heart failure, stroke, myocardial infarction, major cardiovascular events, cardiovascular mortality, and all-cause mortality. The benefits of intensive blood pressure control in patients with moderate to severe hypertension are comparable to those observed in individuals with mild hypertension, with the exception of a reduced impact on all-cause mortality and cardiovascular mortality. Compared with maintaining systolic blood pressure (SBP) above 140 mmHg, SBP below 140 mmHg is associated with a decreased risk of major cardiovascular events in patients aged over 70, as well as a reduced risk of stroke in patients aged 60–69. Furthermore, compared to maintaining SBP above 130 mmHg, SBP below 130 mmHg is linked to a lower risk of major cardiovascular events, heart failure and myocardial infarction in patients over 60, a reduced risk of stroke and cardiovascular mortality in patients aged 60–69, and a decreased risk of all-cause mortality in patients over 70. However, a lower baseline blood pressure or more aggressive blood pressure control may be associated with an increased risk of hypotension.Conclusions Patients with hypertension aged over 60 years can derive benefits from intensive blood pressure management without experiencing significant adverse events, aside from hypotension.